2012
DOI: 10.1080/02701367.2012.10599867
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Emotion on the Control of Low-Level Force Production

Abstract: The accuracy and variability of a sustained low-level force contraction (2% of maximum voluntary contraction) was measured while participants viewed unpleasant, pleasant, and neutral images during a feedback occluded force control task. Exposure to pleasant and unpleasant images led to a relative increase in force production hut did not alter the variability of force production compared to conditions in which participants viewed neutral images. Finding aw discussed with respect to prior work, emphasizing arous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
0
15
1
Order By: Relevance
“…However, based on group differences in FFF2, it is apparent that AWS are more vulnerable to breakdown when speaking under emotionally negative conditions compared to controls. At the same time, some studies using control populations show increases in speed and force production during nonspeech tasks, subsequently leading to an increase in stability [22, 23]. Clearly, more work in this area is needed, particularly in the area of speech-motor control, and with the use of physiological measures for the assessment of autonomic activity related to hedonic valence and arousal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, based on group differences in FFF2, it is apparent that AWS are more vulnerable to breakdown when speaking under emotionally negative conditions compared to controls. At the same time, some studies using control populations show increases in speed and force production during nonspeech tasks, subsequently leading to an increase in stability [22, 23]. Clearly, more work in this area is needed, particularly in the area of speech-motor control, and with the use of physiological measures for the assessment of autonomic activity related to hedonic valence and arousal.…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic increases result in a number of physiological changes, including increases in heart rate and respiration rate [6]. Physiological changes such as these have been shown to impact the motor system, as studies have reported increases in movement speed [25], force production [12, 22], and variability [21, 27] when performing emotionally arousing tasks. Given these previous findings [12, 21, 22, 25], changes in word duration between neutral and emotional conditions were expected; however, this was not the case as there were no within- or between-group differences in word duration across conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It represents subtle finger motion that must be developed in beginner-level dancers according to the above educational guideline. Further, even when the fingers seem to be stationary, the force given by the fingers represents internal emotion and therefore devotion to a theme [ 6 , 7 ], which is unobservable from outside.…”
Section: Introductionmentioning
confidence: 99%